H1‐antihistamine‐refractory chronic spontaneous urticaria: it's worse than we thought – first results of the multicenter real‐life AWARE study. Issue 5 (2nd March 2017) - Maurer, M.; Staubach, P.; Raap, U.; Richter‐Huhn, G.; Bauer, A.; Ruëff, F.; Jakob, T.; Yazdi, A. S.; Mahler, V.; Wagner, N.; Lippert, U.; Hillen, U.; et al.
Summary: Background: Most data on chronic spontaneous urticaria (CSU) originate from highly selected patient populations treated at specialized centres. Little is known about CSU patient characteristics and the burden of CSU in routine clinical practice. AWARE (A World‐wide Antihistamine‐Refractory chronic urticaria patient Evaluation) is an ongoing global study designed to assess chronic urticaria in the real‐life setting. Objective: To describe the baseline characteristics of the first 1539 German AWARE patients with H1‐antihistamine‐refractory CSU. Methods: This prospective non‐interventional study included patients (18–75 years) with a diagnosis of H1‐antihistamine‐refractory CSU for > 2 months. Baseline demographic and disease characteristics, comorbidities, and pharmacological treatments were recorded. Quality of life (QoL) was assessed using the dermatology life quality index (DLQI), chronic urticaria QoL questionnaire (CU‐Q2 oL), and angioedema QoL questionnaire (AE‐QoL, in cases of angioedema). Previous healthcare resource utilization and sick leave data were collected retrospectively. Results: Between March and December 2014, 1539 patients were assessed in 256 sites across Germany. The percentage of females, mean age, and mean body mass index were 70%, 46.3 years, and 27 kg/m 2, respectively. The mean urticaria control test score was 7.9, one in two patients had angioedema, and the most frequent comorbidities were chronic inducible urticaria (CIndU; 24%), allergic rhinitis (18.2%), hypertension (18.1%), asthma (12%), and depression (9.5%). Overall, 57.6% of patients were receiving at least one pharmacological treatment including second‐generation H1‐antihistamines (46.3%), first‐generation H1‐antihistamines (9.1%), and corticosteroids (15.8%). The mean DLQI, total CU‐Q2 oL, and total AE‐QoL scores were 8.3, 36.2, and 46.8, respectively. CSU patients reported frequent use of healthcare resources, including emergency services (29.7%), general practitioners (71.9%), and additional allergists or dermatologists (50.7%). Conclusions and Clinical Relevance: This study reveals that German H1‐antihistamine‐refractory CSU patients have high rates of uncontrolled disease, angioedema, and comorbid CIndU, are undertreated, have impaired QoL, and rely heavily on healthcare resources.